Developmental quotient at 24 months and fatty acid composition of diet in early infancy: a follow up study. Issue 5 (1st May 1997) - Agostoni, Carlo; Trojan, Sabina; Bellù, Roberto; Riva, Enrica; Bruzzese, Maria Grazia; Giovannini, Marcello
Abstract : AIM: A follow up study of developmental quotient (DQ) at 24 months of toddlers whose diets in early infancy differed in fatty acid composition, and in whom an association between diet and DQ was observed at 4 months. METHODS: 81 toddlers were distributed among three groups according to early type of diet: standard infant formula (SFo, n = 30); long chain polyunsaturated fatty acid (LC-PUFA) enriched formula (LCPFo, n  = 26); human milk (HM, n = 25). DQ at 24 months was assessed by Brunet-Lézine's psychomotor developmental test. A subgroup (n = 20; SFo 8; LCPFo 6; HM 6) was tested for erythrocyte phosphatidylcholine and phosphatidylethanolamine. RESULTS: No DQ differences were found by analysis of variance. Neither DQ nor erythrocyte docosahexaenoic acid at 4 months were predictors of DQ scores at 24 months. Phosphatidylcholine arachidonic and docosahexaenoic acid correlated positively, and phosphatidylcholine linoleic acid and phosphatidylethanolamine eicosapentaenoic acid negatively, with DQ. Multiple regression analysis including these variables explained 52% of interindividual DQ variance. A strong association was found between the erythrocyte phosphatidylcholine arachidonic/linoleic acid ratio and DQ ( r = 0.75; p = 0.0001). CONCLUSIONS: The diet/DQ association found at 4 months was not predictive of DQ scores at 24 months. Irrespective of dietary or genetic factors, there appears to be a strong correlation between the LC-PUFA composition of the red cell membrane and higher neurodevelopmental performance.